Comparative financial analysis of plantation teak (Tectona grandis L.f.) under different management practices in farmlands - Shukla, S.R.; Viswanath, Syam (Indian Journal of Agroforestry, 2021)
Globally, teak is an extremely popular timber species and is considered a paragon among timber due to its natural durability, stability and other wood properties. The price trends of teak suggest that there is great demand, which the supply chain is not able to match. In India, traditionally teak plantations have been raised by forest departments in forest land under specific management practices on long rotations (>40 years). For over the past couple of decades, there has been considerable interest among farmers to grow teak on farm boundaries and in block plantations at shorter rotations considering its high price and great demand in the market. However, adequate scientific studies have been lacking on management inputs and wood quality as well as the ideal rotation period. Present work reports the financial viability of farm teak raised across three regimes; viz., partially managed line (Lpm), unmanaged block (Bum) and intensively managed block (Bim) plantations in Karnataka, India. Unlike Bim, Lpm was not subjected to any special silvicultural management practice. Previous studies by the authors on the same plantation models at 12-year-age had projected that Lpm at 20-years could have the highest equated annual income (EAI) and was identified as a promising prospect from a financial perspective. However, financial analysis performed on the same models based on actual growth rates (MAI) at 24-25-year age indicated that EAI from Bim appeared to be relatively higher than Lpm and Bum. Since input costs varied across these regimes, there were considerable variations in benefit to cost (B/C) ratio and EAI suggesting that Bim may be the most financially viable practice for growing teak in farmlands. Due to the relatively lower growth of Bum, total extractable wood volume was smaller compared to Lpm and Bim. Considering the financial parameters at 8 and 12% discount rates, it is concluded that retaining farm teak trees beyond 25-year age under any of the three practices studied may not be financially prudent.